China – Mauritius FTA in 2019: a Perspective From Economic Motives: A PERSPECTIVE FROM ECONOMIC MOTIVES - Wahyutomo, Naomi Theodora (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
ABSTRACT This article aims to explore China’s economic motives in China – Mauritius FTA which was signed in 2019 and implemented in 2021. This article tries to answer the research question which is why did China make an FTA with Mauritius despite of insignificant trade between both countries. This article uses Mireya Solís’ and Saori N. Katada’s Cross-Regionalism theory, specifically economic motives that consist of two indicators which are open a new market and/or expand market and avoid trade diversion, to answer the research question. This research uses qualitative method and literature study. The result shows that China’s economic motives in China – Mauritius FTA are to expand market to Africa through Mauritius and to avoid trade diversion from China to other countries such as India as one of a biggest trade partner of Mauritius. Moreover, this article also links the economic motives to China’s ambition as a global economic power through its big project named Belt and Road Initiative (BRI). Keywords: China, Cross-Regionalism, FTA, Mauritius, Trade